Improving Citation Analysis: Taking Account of Order of Authors and Number of Different Articles in Which a Scholar Is Cited - Cohn, Ellen G. (Journal of contemporary criminal justice, 2023)
Research using citation counts as a metric for measuring scholarly influence and prestige generally gives equal weighting to all authors of a scholarly work. However, as the order of authors frequently reflects the relative importance and involvement of authors, it may be more valid to consider this issue when examining citations. This article focuses on citations in Criminology and gives authors a score based on their order in the author list. Only the first five authors in each reference are counted, so the first author is given a score of 5, the second author a score of 4, and so on. In addition, citation analysis typically counts the total number of citations, rather than the number of different articles in which a scholar is cited. Arguably, the number of different articles is a more valid measure because it shows how many other authors are influenced by a scholar. A large number of citations in a small number of articles may reflect a relatively small amount of scholarly influence. This article shows the effect of counting the number of different articles in which a scholar is cited. We argue that citation analysis would be improved by taking account of the order of authors and the number of different articles.